Phenological study of Pilocarpus microphyllus Stapf Ex Wardleworth germplasm correlated with climatic elements (Research, Society and Development, 2021)
The Pilocarpus microphylus Stapf Ex Wardleworth-Rutaceae, is known as true jaborandi for presenting high levels of pilocarpine in its leaves, which motivates its collection intensely. There is a direct relationship between phenophasic events, such as flowering and fruiting, with local environmental conditions, and it is important to interpret the relationship between them. The objective of this work was to characterize the reproductive phenophases of Jaborandi belonging to the Active Germplasm Bank of Embrapa Amazônia Oriental, correlating with the meteorological elements, in order to indicate the most appropriate time for the collection and use of the plant material of the species. were recorded weekly from 2015 to 2019. According to the phenological activity, both phenophases occurred in 97% of the accessions studied. And the Spearman correlation index showed a significant negative correlation between the occurrence of phenophases and the mean air temperature. Phenophases occurred in all months of the year, indicating high seasonality. The highest averages were recorded in March, corresponding to the moment of greatest recorded rainfall, and the lowest average values ​​occurred in January, with mild temperatures, for both phenophases evaluated. It is suggested to collect plant material of the species for medicinal use from July to February, whose registration of the number of days that the phenophases occur is reduced. It is pertinent to carry out further studies on the correlation of phenology with climatic events considering the performance of each access individually.